Architecture and industrialization - Chumpitaz Mellarez, Felipe (2024)
The industrialization of construction proposes the optimization of processes through the implementation of technologies such as BIM, artificial intelligence and 3D printing, which have transformed the planning and execution of projects, promoting greater and earlier integration of all the disciplines involved, with more efficient and encouraging results. In Peru, initiatives such as Plan Selva (2015) have demonstrated the tremendous potential of combining modern technology with traditional solutions to optimize construction systems for hard-to-reach areas. This article explores the concepts of industrialization in architecture, modular design and the use of local resources as a response to contemporary concerns and demands. In this sense, the aim is to seek a democratic, avant-garde and sustainable architecture, capable of recognising both the heritage and accumulated knowledge as well as technological and industrial advances, in order to respond effectively and forcefully.